2017
DOI: 10.1038/srep46566
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs2Pathways: Identifying the pathways influenced by a set of lncRNAs of interest based on a global network propagation method

Abstract: Long non-coding RNAs (lncRNAs) have been demonstrated to play essential roles in diverse cellular processes and biological functions. Exploring the functions associated with lncRNAs may help provide insight into their underlying biological mechanisms. The current methods primarily focus on investigating the functions of individual lncRNAs; however, essential biological functions may be affected by the combinatorial effects of multiple lncRNAs. Here, we have developed a novel computational method, LncRNAs2Pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 76 publications
(124 reference statements)
0
21
0
Order By: Relevance
“…Identification of the potential signaling pathways that lncRNAs regulate is critical from a therapeutic point of view. In some cases, deciphering the signaling pathway and its upstream or downstream regulators can indicate the mechanisms used by a specific lncRNA (29). In this study, VINAS and DEPDC4 knockdown in cytokine-activated ECs reduced the phosphorylation of IκBα and p38 MAPK while having no significant effects on phosphorylation of the AKT signaling pathway (Figure 4).…”
Section: Discussionmentioning
confidence: 64%
“…Identification of the potential signaling pathways that lncRNAs regulate is critical from a therapeutic point of view. In some cases, deciphering the signaling pathway and its upstream or downstream regulators can indicate the mechanisms used by a specific lncRNA (29). In this study, VINAS and DEPDC4 knockdown in cytokine-activated ECs reduced the phosphorylation of IκBα and p38 MAPK while having no significant effects on phosphorylation of the AKT signaling pathway (Figure 4).…”
Section: Discussionmentioning
confidence: 64%
“…We also compare our results with LncRNAs2Pathways [53]. LncRNAs2Pathways is an R-based tool under a LncPath package name.…”
Section: Comparison For the Pathway Enrichment Resultsmentioning
confidence: 97%
“…The importance of cytoskeleton-associated proteins and pathways involved in glioma has also been reported in numerous previous studies ( 27 , 28 ). In addition, increasing evidence revealed that lncRNAs are associated with the occurrence and development of glioma by regulating the structure of reorganization of cytoskeleton-associated proteins and signaling pathways ( 29 , 30 ). Additionally, the association between metastasis or cytoskeleton and the prognosis of glioma has also been reported ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%